Programmable Electrofabrication of Porous Janus Films with Tunable Janus Balance for Anisotropic Cell Guidance and Tissue Regeneration. (11th March 2019) - Lei, Miao; Qu, Xue; Liu, Huan; Liu, Yi; Wang, Shijia; Wu, Shang; Bentley, William E.; Payne, Gregory F.; Liu, Changsheng
Abstract: Janus films with controlled pore structures can be particularly important in diverse applications. There remains a challenge for simple, rapid, and scalable fabrication methods to control Janus balance (JB) including the thickness of the individual face as well as porosity and pore size. Here the electrofabrication of a porous Janus film with controlled Janus balance from aminopolysaccharide chitosan under the salt effect is reported. Sequential deposition of chitosan under programmable salt environment and electrochemical conditions enables construction of Janus films with precisely controlled Janus balance. Bioactive partially soluble calcium phosphate (CaP) salts can also generate porous structure in Janus film. It is specifically reported that a chitosan/hydroxyl apatite (HAp) composite Janus film can serve as an effective scaffold for guided bone regeneration. The dense layer functions to provide mechanical support and serves as a barrier for fibrous connective tissue penetration. The porous composite layer functions to provide the microenvironment for osteogenesis. In vivo studies using a rat calvarial defect model confirm the beneficial features of this Janus composite for guided bone regeneration. These results suggest the potential of electrofabrication as a simple and scalable platform technology to tune the self‐organization of soft matter for a range of emerging applications. Abstract : We report the use of electrical signals to sequentially create a Janus film with a dense and a porous layer. This fabrication method enlists the stimuli‐responsive self‐assembling behaviors of chitosan in the presence of varied salt species. This water‐based fabrication method is simple and rapid and allows for independent tuning of the Janus Balance under pre‐programmable ionic environment and electrical signals.